A Polyphenol-Rich Extract from Muscadine Grapes Prevents Hypertension-Induced Diastolic Dysfunction and Oxidative Stress - Pooja D. Patil; Ana Clara Melo; Brian M. Westwood; E. Ann Tallant; Patricia E. Gallagher (MDPI AG, 2022)
Muscadine grapes are abundant in dietary polyphenols, but their effect on hypertension-induced cardiac damage is limited. This study assessed whether a muscadine grape skin/seed extract supplement (MGES) prevents hypertension-induced cardiac damage and oxidative stress. Male Sprague Dawley rats were treated for four weeks with drinking water, angiotensin II (Ang II) to induce hypertension, MGES, or both Ang II and MGES. Cardiac function assessed by echocardiography showed that Ang II increased systolic blood pressure while MGES alone or in combination with Ang II had no effect. Ang II increased E/e', an indicator of left ventricular filling pressure and diastolic dysfunction, by 41% compared to Control and co-treatment with MGES prevented the Ang II-mediated increase, suggesting that the extract attenuated hypertension-induced diastolic function. Ang II infusion increased urinary 8-hydroxy-2'-deoxyguanosine and cardiac 4-hydroxynonenal and malondialdehyde, which were prevented by the extract. The antioxidant enzymes catalase and superoxide dismutase 1 activity and mRNA were increased significantly in animals treated with MGES alone or in combination with Ang II, suggesting that the extract upregulates oxidative stress defense mechanisms in cardiac tissue. Thus, MGES may serve as a medical food to protect the heart from hypertension-induced diastolic dysfunction caused in part by excessive reactive oxygen species production.